The Modification Formula of Manggaraian Traditional Food â€œRebok Sikisekoâ€ - Chelsia Wihelmina Edam; A.A Made Semariyani; Ni Made Ayu Suardani Singapurwa (SEAS (Sustainable Environment Agricultural Science), 2019)
This study aims to determine the effect of comparison of corn flour and grated coconut and the addition of liquid margarine to the characteristics of "rebok sikiseko". The design used is a Completely Randomized Design (CRD) with two factors and two replications, namely the first-factor comparison of cornflour and grated coconut which consists of three levels: 3:1; 2:2; 1:3. The second factor is the addition of liquid margarine which consists of 3 levels: 100 ml, 125 ml, 150 ml. Objective observations include water content, protein content, fat content, ash content, carbohydrate content, crude fiber content and subjectively including color, texture, aroma, taste, and overall acceptance. The best research results obtained in the treatment of cornflour and grated coconut 1:3 with the addition of 100 ml margarine produce a water content of 5.73%, protein content of 5.28%, fat content of 29.21%, ash content of 0.54%, fiber content roughly 4.00%, carbohydrate content 59.25%, and subjectively obtained the highest favorite value from panelists.